Cooperative Photochemical Reaction Kinetics in Organic Molecular Crystals. Issue 14 (12th January 2023) - Morimoto, Kohei; Kitagawa, Daichi; Bardeen, Christopher J.; Kobatake, Seiya
Abstract: Photoreactive molecular crystals have been intensively investigated as next‐generation functional materials. Changes in physicochemical properties are usually interpreted in terms of static pre‐ and post‐reaction molecular structures and packings determined by X‐ray structure analysis. However, to elucidate the dynamic properties, it is necessary to understand the dynamic nature of photochemical kinetics in crystals. Reaction dynamics in the crystal phase can be dramatically different from those in dilute solution because the local molecular environment evolves as the surrounding reactant molecules are transformed into products. In this Review article, we summarize multiple examples of photochemical reactions in the crystalline phase that do not follow classical kinetic behavior. We also discuss different theoretical methods that can be used to describe this behavior. This Review article should help provide a foundation for future workers to understand and analyze photochemical reaction kinetics in crystals. Abstract : In organic molecular crystals, many photoreactions do not obey simple kinetic models, but instead follow nucleation‐growth kinetics. This kind of reaction is often called a cooperative reaction because the reaction of an individual molecule is facilitated (or inhibited) by its neighbors.